2015
DOI: 10.1103/physrevb.92.014421
|View full text |Cite
|
Sign up to set email alerts
|

Microwave multimode memory with an erbium spin ensemble

Abstract: Hybrid quantum system combining circuit QED with spin doped solids are an attractive platform for distributed quantum information processing. There, the magnetic ions serve as coherent memory elements and reversible conversion elements of microwave to optical qubits. Among many possible spin-doped solids, erbium ions offer the unique opportunity of a coherent conversion of microwave photons into the telecom C-band at 1.54 µm employed for long distance communication. In our work, we perform a time-resolved elec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
94
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 52 publications
4
94
1
1
Order By: Relevance
“…This can be used to interface microwave photons to a RE doped crystal through a superconducting resonator 22,23 and obtain quantum memories for superconducting qubits. [24][25][26] In this case too, nuclear hyperfine transitions can provide long storage time. We recently showed that 145 Nd 3+ :Y 2 SiO 5 hyperfine transitions have ground state coherence lifetimes up to 9 ms at 5 K, whereas the electron spin T 2 is about 100 µs.…”
Section: -4mentioning
confidence: 99%
“…This can be used to interface microwave photons to a RE doped crystal through a superconducting resonator 22,23 and obtain quantum memories for superconducting qubits. [24][25][26] In this case too, nuclear hyperfine transitions can provide long storage time. We recently showed that 145 Nd 3+ :Y 2 SiO 5 hyperfine transitions have ground state coherence lifetimes up to 9 ms at 5 K, whereas the electron spin T 2 is about 100 µs.…”
Section: -4mentioning
confidence: 99%
“…Such memo ries offer the possibility exploiting electron spin coherence times of up to seconds [3] as a resource for superconducting qubits, whose coherence times so far extend only to tens of microseconds [4], Strong coupling has been observed between superconducting resonators and various paramag netic impurities, including NV centers in diamond [5] and erbium ions in Y2S i0 5 (YSO) and YA103 [6][7][8], leading to reversible coherent storage of (large numbers of) microwave photons within spin ensembles [9,10]. These para magnetic impurities are often coupled to nuclear spins that can offer a further resource for storage-electronic spin coherences can be transferred to and from a nuclear spin [11][12][13], to access coherence times as long as hours [14],…”
mentioning
confidence: 99%
“…(3) is evaluated in this limit the expressions reduce to the first-order lumped-circuit treatments described in the literature for a single resonator in transmission. 11,12,38 However, we find that to faithfully reproduce the interactions between resonators over a wide spectral bandwidth the full functional form presented here is required.…”
Section: Phenomenological Resonator Modelmentioning
confidence: 99%